Memotret E-Procurement dalam Mewujudkan Good Governance di Indonesia - Budi Chrismanto Sirait (Journal of Governance, 2018)
Abstract: This study intends to reveal the advantages as well as the weaknesses of the implementation of the concept of good governance in changing the workings of the bureaucracy as a public servant and the lack of bureaucratic ability to involve the community through public consultation. The method used is qualitative with descriptive-analytical methodology, which aims to describe, record, analyze, and interpret the conditions that occur about concepts such as bureaucracy as an extension of the state in exercising its authority, and governance as a basic guide in the management of public sectors which was done in this period was used to limit the process of mutual bonding between the community and the regional government bureaucracy. The results and findings of this paper are in the form of literature review based on the study of the implementation of e-procurement that has been done in several local governments in Indonesia, namely the emergence of the concept of governance, which mengintroduksikan the idea of ending the state domination in managing public life, it can be read as an effort from the countries superpower to perfect the ideology of liberal democracy that has been widely embraced by developing countries including Indonesia.Keywords: Governance, E-Procurement, Bureaucracy and Public Policy. Abstrak: Studi ini bermaksud untuk mengungkap kelebihan sekaligus kelemahan dari implementasi konsep good governance dalam merubah cara kerja birokrasi sebagai pelayan masyarakat dan lemahnya kemampuan birokrasi untuk melibatkan masyarakat melalui konsultasi publik. Metode yang digunakan adalah kualitatif dengan metodologi deskriptif-analisis, yang bertujuan untuk menggambarkan, mencatat, menganalisa, dan menginterpretasikan kondisi yang terjadi mengenai konsep-konsep seperti birokrasi sebagai perpanjangan tangan negara dalam melakukan otoritasnya, dan governance sebagai panduan dasar dalam pengelolaan sektor-sektor publik yang dilakukan pada masa ini ternyata dipergunakan sebatas untuk mendetailkan proses terjalinnya ikatan timbal-balik antara masyarakat dengan birokrasi pemerintahan daerah. Hasil dan temuan dari tulisan ini adalah berupa literature review berdasarkan kajian dari penerapan e-procurement yang telah dilakukan di beberapa pemerintahan daerah di Indonesia yaitu munculnya konsep governance yang mengintroduksikan ide diakhirinya dominasi negara dalam mengelola kehidupan publik. Hal tersebut merupakan upaya ideologi demokrasi liberal yang mulai banyak dianut oleh negara-negara berkembang termasuk Indonesia.Kata Kunci: Governance, E-Procurement, Birokrasi dan Kebijakan Publik.